Activities and metabolomics of Cordyceps gunnii under different culture conditions - Qu, Shuai-Ling; Xie, Juan; Wang, Jun-Tao; Li, Guo-Hong; Pan, Xue-Rong; Zhao, Pei-Ji (Frontiers in Microbiology, 2023)
Many active metabolites have been identified from various species of the fungal genus Cordyceps. A predominant species of this genus is Cordyceps gunnii, but there are limited reports on the active ingredients from this species. This study aimed to conduct activity assays and metabolome analysis on extracts of C. gunnii obtained under different culture conditions. Five different solid media were selected to culture the mycelium of C. gunnii and the metabolites were extracted with organic solvents; concurrently, the wild stroma and host complexes of C. gunnii were extracted by ethyl acetate. Extracts were subsequently assayed for various biological activities and were analyzed by untargeted metabolomics. There were significant differences in the activities and metabolites of C. gunnii extracts from different culture conditions and from wild stroma and host complexes. The extracts of stroma and host complexes and mycelia cultured on WGA medium for 21 days exhibited similar effective inhibitory activity against five cell lines. A total of 51 metabolites were annotated and included various structural types. The literatures indicate that most of the identified compounds have a variety of different biological activities. These findings provide the basis for further systematic excavation of C. gunnii and improved utilization of this fungal species.